1974
DOI: 10.1104/pp.54.5.780
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Method for the Isolation of Spinach Chloroplast Envelope Membranes

Abstract: A three-phase, discontinuous sucrose gradient yielded two distinct fractions of envelope membranes from spinach (Spinacia oleracea L.) chloroplasts. Their buoyant densities were 1.08 g cm-' and 1.11 g cm-3. Electron micrographs showed the lighter and heavier fractions to consist primarily of single and double membranes, respectively. The milligrams of lipidmilligrams of protein ratio for the complete envelope membrane (double membrane fraction) was 1.74. Thin layer chromatograms showed that the lipids of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 17 publications
(20 reference statements)
3
33
0
Order By: Relevance
“…Intact chloroplasts for each species were prepared from 40, 80, or 120 g of leaves as above. Buoyant densities of incomplete and complete envelope membranes (22) were determined on a continuous sucrose gradient. Their properties were sufficiently similar so that preparations from each of the species could be prepared by the same procedure developed for isolating spinach chloroplast envelope membranes (22).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intact chloroplasts for each species were prepared from 40, 80, or 120 g of leaves as above. Buoyant densities of incomplete and complete envelope membranes (22) were determined on a continuous sucrose gradient. Their properties were sufficiently similar so that preparations from each of the species could be prepared by the same procedure developed for isolating spinach chloroplast envelope membranes (22).…”
Section: Methodsmentioning
confidence: 99%
“…A comparison of the biochemical properties of chloroplast envelope membranes from species with different photosynthetic rates might show differences in the permeability properties and help elucidate the operations of translocators. To this end chloroplast envelope membranes from leaves of the less efficient species, spinach and broad bean, have been isolated and partially characterized in several laboratories (4,11,12,19,22). No descriptions of the properties of isolated chloroplast envelope membranes from more efficient species, sunflower or maize, have previously been reported.…”
mentioning
confidence: 99%
“…For comparison the quantity and fatty acid composition of the complete and incomplete envelope fractions prepared from intact chloroplasts by the method of Poincelot and Day (12) As a further check on the distribution of chloroplast envelope fragments in our homogenates, the centrifugal fractions were analyzed for Mg2"-dependent DCCD-insensitive ATPase, a high specific activity of which has been previously shown to be characteristic of envelopes (4,11,14). This enzyme was found to be present at a high specific activity in the 10,000g, 40,000g, and 144,000g fractions ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The intactness of the chloroplasts was determined by phase contrast microscopy, the intact fraction containing 90 to 95% bright and highly refractile chloroplasts, and the broken fraction containing only chloroplasts with distinct grana visible. Chloroplast envelopes were prepared from intact chloroplasts by osmotic shock and sucrose gradients as described by Poincelot and Day (12). They obtained two fractions (complete and incomplete envelopes) although no electron microscope study was made in this case. Lipids from all of these fractions were extracted, separated, and analyzed quantitatively and for radioactivity as previously described (19)(20)(21) (1).…”
Section: Methodsmentioning
confidence: 99%
“…St. John et al (30) have shown that BASF 13.338 treatment reduced the tolerance of cotton to chilling injury, prevented frost hardening in wheat, barley, and rye and induced greater resistance in Sorghum and corn to high temperature stress. Contrary to these observations, Ashworth et aL (3) (21). The chloroplast pellet was suspended in 20 mM with swirling and homogenized by giving three complete passes in a Teflon homogenizer.…”
mentioning
confidence: 99%